This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Before anything else, the sum is absolutely convergent since we have \substack k ≥ 1 n ≥ 0 ∑ k ( k ⋅ 2 n + 1 ) 1 < k ≥ 1 ∑ k − 2 n ≥ 0 ∑ 2 n 1 = 6 π 2 ⋅ 2 < ∞ . Thus we may swap the order of summation.
We use d = k ⋅ 2 n + 1 ≥ 2 as the summation variable, so that the sum in question is d ≥ 2 ∑ d 1 \substack k ∃ n : d − 1 = k ⋅ 2 n ∑ k ( − 1 ) k − 1 . Now we claim that the inner sum is exactly d − 1 1 . Indeed, if d − 1 = 2 r m + 1 with m odd, then the sum is m ( − 1 ) m − 1 + 2 m ( − 1 ) 2 m − 1 + ⋯ + 2 r m ( − 1 ) 2 r m − 1 &= m 1 ( 1 1 − 2 1 − ⋯ − 2 r 1 ) &= 2 r m 1 &= d − 1 1 . Consequently, the final answer is d ≥ 2 ∑ d ( d − 1 ) 1 = d ≥ 2 ∑ ( d − 1 1 − d 1 ) = 1 .